When should I choose a mixed methods approach? - Creswell, John W. ([Thousand Oaks, Calif. : SAGE], 2010)
The speaker analyses the choice of a mixed methods approach to social research rather than a quantitative or qualitative one.
"SAGE research methods online."
Title from home page (viewed Jan. 26, 2011).
Online video.
Includes transcript.
Specialized.
Mode of access: World Wide Web.
Keywords: elektronické knihy; electronic books; Mixed methods research